STRATEGI KEPALA SEKOLAH BERBASIS BUDAYA POSITIF DALAM PENCEGAHAN BULLYING PADA SEKOLAH DASAR GUGUS III TENGKU RAJA SAYED KECAMATAN MANYAK PAYED KABUPATEN ACEH TAMIANG - Nova, Aswita; Munawar, Munawar; Mukhlisuddin, Mukhlisuddin (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to 1) What is the principal's strategy in building a positive culture to prevent bullying, 2) What are the challenges of the principal in a positive culture towards bullying prevention, 3) What is the impact of implementing a positive culture on the learning environment and interactions between school members. This study uses qualitative research. Data collection techniques use interviews, observation and documentation. While the data analysis technique uses data reduction, data presentation, and drawing conclusions/verification. The research subjects of the Tengku Raja Sayed Cluster III, Manyak Payed District, Aceh Tamiang Regency, namely: Geulanggang Merak State Elementary School, Raja Tuha State Elementary School and Simpang Tiga State Elementary School. The results of this study indicate that the principal's strategy based on a positive culture in preventing bullying at Tengku Raja Sayed Cluster III Elementary School has generally been running in harmony and mutually reinforcing between the principal, teachers, students, and parents. This harmony is evident in the shared understanding of the importance of creating a safe, comfortable, and conducive school environment for the social and emotional development of students. However, this study also found partial asynchronization, especially in the aspects of collaboration and socialization which have not been specifically and sustainably programmed.